Microbiological parameters indicators of the effect of diuron on soil microflora - Vieira, Rosana Faria (Pesquisa Agropecuaria Brasileira, 1999)
Microbial biomass (Cmic), basal respiration (BR), Cmic:Corg ration and the qCO2 were used to evaluate the influence of 0, 2 and 20 mg g-1 of the herbicide diuron on the soil microflora. The study was carried out with two soil types. Evaluations were made at 0, 3, 10, 20 and 33 days after the herbicide application. In the more clayed soil, the Cmic and the ration Cmic:Corg gave similar results in relation to the effect of diuron. The BR was not affected by diuron application. The qCO2 was the only parameter able to demonstrate a differentiation between the doses. In the more sandy soil it was not possible to detect any effect of the herbicide.